The unquiet western front : - Bond, Brian (Cambridge University Press, 2002)
Britain's role in the First World War has been portrayed through literature, films and plays with a marked un-historical, anti-war spirit. Deeply-rooted myths have thus become dominant and historians have either endorsed them, or have written narrowly for other specialists. As a result of the opening of official military archives and more objective study, these portrayals are now being challenged. This book traces the controversy from 1918 to the present, concluding that historians are finally permitting World War I to be placed in a more accurate perspective.